INDOOR AND OUTDOOR AIR QUALITY OF POULTRY FARM AT BANGALORE - R. PAVAN; K. MANJUNATH (International Journal of Pharma and Bio Sciences, 2014)
The present study was to determine the concentration, in terms of monthly and seasonal distribution and in relation to meteorological factors, of indoor and outdoor airborne fungal spores in poultry farm at Bangalore. Samples were collected at fortnightly for a period of one year in duplicates between January 2011 to December 2011 by using Andersen two stage viable air sampler petri plates containing Malt Extract Agar media to the air for 5 minutes. A total of 16912.23 CFU/m3 fungal species was isolated from the indoor (80662.52 CFU/m3) and outdoor (8849.71 CFU/m3) of the poultry farm. In indoor 22 species belonging to 12 genera and 18 species belonging to 11 genera from outdoor of the poultry farm. The dominant fungal species were Cladosporium, Penicillium and Alternaria from indoor and outdoor respectively. Correlation between seasonal and meteorological factors were carried out. An attempt has been made to forecast atmospheric fungal spores concentration in poultry farm.